(untitled) (Research, Society and Development, 2021)
Medicinal plants are resources of first choice for many population groups with restricted access to government public health programs. Such plants are easily found and sold in open-air markets and public markets in a fresh or dry way, being considered a cultural practice. This work aimed to identify the medicinal plants sold in an open market and in the Municipal Public Market of Iguatu, in the State of Ceará, Brazil, to present their therapeutic indications, active principles and means of transmission of this knowledge by herbs traders. Based on the qualitative and quantitative approach, making use of semi-structured interviews with herbs traders, a survey of medicinal plants was carried out using the free listing technique. From the specialized literature, it was possible to identify the botanical species sold. The results of the research allowed the identification of 59 ethnospecies, belonging to 55 genera and distributed in 38 botanical families, with Fabaceae and Lamiaceae being the most representative families, both with 8.5%, followed by Asteraceae with 6.5%. Regarding the most used vegetable part, bark, and stems (27.42%) and seeds (24.19%) stood out and the predominant method of preparation was tea (98.3%). Among the species cited by herbs traders, 22% are used to treat more than one health problem, while 78% have only one therapeutic indication. As for the sanitary conditions, some inadequate conditions of storage of plant materials for commercialization were observed.